Gender, Democratic Governance and Development in Nigeria - Enojo , Enojo Kennie (African Journal of Education,Science and Technology (AJEST), 2015)
Women constitute about half of the world‘s population and have contributed monumentally to the promotion of the human race (Enojo, 2012). In Nigeria, for instance, women, have always played five major key roles either as a mother, producer, home manager, community organizer, and or social, cultural and political activist. Despite their numerical strength, endowed resources and crucial functions, the divisions of roles between the male and female sexes, as prescribed by most cultures, assign the subordinate position to women and consigned them to the background of history. As a consequence, women in different occasion have for long suffered various forms of discrimination, exploitation, inequality, exclusion and structural violence thereby limiting the democratic space, governance and national development. The aim of this paper is to encourage and empowered women as a precondition for and as an indicator for sustainable national development. The objectives include identifying and analyses the possible causes, factors and conditions which impend women participation in democratic leadership and development. Our finding shows that most women are either ignorant of their potentials or failed to accept their roles as prescribed by nature as veritable agents of positive and constructive change. Aside this factor is the issue political violence, money-bag, god-fatherism and lack of internal democracy associated with the Nigerian politics. Finally, that gender differences are created and sustained by society through its traditions, customs, conventions, norms and regulations (Ukamaka, 2012). The conclusion is that traditional stereotypes that characterize women as submissive, illogical, passive and emotional are not empirically founded and is therefore referred to as preposterous thesis. We therefore recommend that women should be encouraged to fully participate in democratic governance and sustainable national development in Nigeria, if we are to be to move our political and economic interest to greater heights without prejudice or ideological cover.